CGIAR Climate Change Impact Platform Bi-Monthly Newsletter, Edition 1, January-February 2024 - Edward-Uwadiale, Regina; Mukherji, Aditi (CGIAR Climate Change Impact Platform, 2024)
Welcome to the inaugural edition of our Climate Impact Platform Bi-monthly newsletter, where we will showcase Platform activities, share impactful climate stories from CGIAR Research Centers, bilateral projects, and ongoing Initiatives, feature CGIAR climate scientists, and keep you informed of upcoming events and key moments. Please send us information about your recent publications to be curated as a part of Climate Insights or progress reports from your projects and Initiatives to be featured in our bi-monthly newsletter.